1996
DOI: 10.1128/jcm.34.3.516-519.1996
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of enterohemorrhagic Escherichia coli O157 strains from patients with hemolytic-uremic syndrome by using immunomagnetic separation, DNA-based methods, and direct culture

Abstract: We examined 30 children with classical hemolytic-uremic syndrome (HUS) for the presence of enterohemorrhagic Escherichia coli (EHEC) strains in stool samples and determined the specific immune response to O157 lipopolysaccharide in acute-phase serum samples from these patients. EHEC O157 strains were isolated from stool samples of 18 (60%) of the patients, and non-O157 EHEC strains were isolated from 5 (17%) of the patients. For O157 strain isolation from stools, we introduced a selective enrichment step using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…With the exception of an Enterococcus faecalis isolate, these strains grew well in mTSB + a. 0157 VTEC, but some sorbitol-fermenting E. coli 0157:NM do not grow on CT-SMAC (Karch et al 1996). Almost all 0157 STEC lack GUD activity and to exploit this characteristic, media that contain the fluorogenic compound, 4-methylumbelliferyl-fJ-D-glucuronide (MUG) (Szabo et al 1986;Okrend et al 1990a) or the chromogenic compound 5-bromo-4-chloro-3-indolyl-fJ-D-glucoronide (BCIG) (Okrend et al 1990b), were developed.…”
Section: Enrichment Mediamentioning
confidence: 97%
“…With the exception of an Enterococcus faecalis isolate, these strains grew well in mTSB + a. 0157 VTEC, but some sorbitol-fermenting E. coli 0157:NM do not grow on CT-SMAC (Karch et al 1996). Almost all 0157 STEC lack GUD activity and to exploit this characteristic, media that contain the fluorogenic compound, 4-methylumbelliferyl-fJ-D-glucuronide (MUG) (Szabo et al 1986;Okrend et al 1990a) or the chromogenic compound 5-bromo-4-chloro-3-indolyl-fJ-D-glucoronide (BCIG) (Okrend et al 1990b), were developed.…”
Section: Enrichment Mediamentioning
confidence: 97%
“…Bacteria with beads attached are separated by magnetic force and plated onto SMAC agar and on a selective cefixime-tellurite (CT)-SMAC agar. The study performed in our laboratory [45] demonstrated that the IMS technique was able to detect 10 2 of E. coli O157/g of feces in the presence of 10 7 of background coliform flora and significantly increased the isolation rate of E. coli O157 from stool as compared with direct plating.…”
Section: Isolation Of Stec O157:h7mentioning
confidence: 88%
“…However, this is often not possible, especially in HUS patients in whom the number of STEC O157:H7 in stool can be very low when HUS is diagnosed (usually 1 week or later after the onset of prodromal diarrhea). To increase the sensitivity of the isolation of STEC O157 in such cases, selective enrichment using the technique of immunomagnetic separation (IMS) is recommended [45]. In the IMS procedure, fecal samples are enriched in GN Broth Hajna for 4±6 hours and then incubated with magnetic beads coated with anti-O157 antibody.…”
Section: Isolation Of Stec O157:h7mentioning
confidence: 99%
“…The sensitivities of PCR techniques to detect E. coli 0157 and other foodborne pathogens are dependent on many factors. Previous procedures differed in the type of DNA recovery technique used (Lindqvist 1997;Venkateswaran et al 1997); the PCR parameters (Chen et al 1998;Stone et al 1995;Wang et al 1997); the type of sample (Karch et al 1992;Stone et al 1995;Witham et al 1996); and the physiological state of the cells (Uyttendaele et al 1998). The PCR-LS-SOB and PCR-7200 procedures differed in the amount of MgCl, used, the thermal cycling conditions, and the plate readers.…”
Section: Discussionmentioning
confidence: 99%
“…Other genes, such as the eaeA gene also have been used as primer targets for the detection of E. coli 0157:H7 (Fratamico et al 1995;Gannon et al 1997;Paton and Paton 1998). Because the srx genes are subject to frequent loss during cultivation (Karch et al 1992), the eaeA gene may be a better predictor of the presence of enterohemorrhagic E. coli 0157:H7 (Gannon et al 1993). Simultaneous detection of multiple genes of this pathogen in a multiplex PCR has been reported (Franck et al 1998;Fratamico et al 1995;Gannon et al 1992Gannon et al , 1997Meng et al 1997;Paton and Paton 1998).…”
Section: Introductionmentioning
confidence: 99%